Screening for dementia: Fluidity and the Mini Mental State Examination in India - Brijnath, Bianca (2011)
The Mini Mental State Examination (MMSE) is a popular screening instrument for dementia. Drawing on ethnographic data from India, three vignettes are presented to examine how the MMSE is operationalised by interviewers and respondents. Using the concept of 'fluidity' from Science and Technology Studies, it will be demonstrated that the MMSE is fluid and changes according to individual norms, institutional resources, and cultural settings. In some environments, the scores are discounted in order to count; in others, the scale is perceived as an invitation to talk; and finally, the MMSE can also operate as an entry-point to seek treatment for other psychological concerns.